Composite for secondary batteries, composite sheet for secondary batteries and method of manufacturing the same, and secondary batteries
The use of a fibril-like resin binder with specific properties in secondary battery composites addresses binding issues, improving ion conductivity and active material content, resulting in a high-performance composite sheet for secondary batteries.
Patent Information
- Application Number
- KR1020247029488
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-03-02
- Filing Date
- 2023-03-02
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-03-02
AI Technical Summary
Existing secondary battery composites face challenges in achieving optimal performance due to insufficient fibrillation of binders, leading to poor binding properties and reduced active material content, which affects ion conductivity and overall battery efficiency.
A composite for secondary batteries is developed using a fibril-like resin with a fibril diameter of 100 nm or less as a binder, incorporated in an amount of 0.3 to 8 mass%, and a powdered polytetrafluoroethylene resin with specific gravity of 2.12 to 2.20, applied through processes involving shear mixing and calendering or extrusion to create a composite sheet.
The solution enhances battery performance by improving ion conductivity, reducing moisture content, and increasing active material content, resulting in a composite sheet with higher strength and flexibility, thus enhancing battery efficiency.
Smart Images

Figure 112024095987761-PCT00001 
Figure 112024095987761-PCT00002 
Figure 112024095987761-PCT00003
Abstract
Description
Technology Field
[0001] The present disclosure relates to a composite for a secondary battery, a composite sheet for a secondary battery, a method for manufacturing the same, and a secondary battery. Background Technology
[0002] In lithium-ion secondary batteries, a secondary battery sheet is generally produced by coating and drying a slurry obtained by mixing an electrode active material and a conductive aid with a binder and a solvent.
[0003] Meanwhile, fibrilable resins such as polytetrafluoroethylene resin are also used, and by fibrillating them, they are used as binders.
[0004] Patent Document 1 discloses a method for producing an electrode in which polytetrafluoroethylene is fibrillated by treating a mixture comprising an active material and a polytetrafluoroethylene mixed binder material with a high shear using a jet mill.
[0005] Patent Document 2 discloses obtaining an all-solid-state lithium-ion secondary battery by using a specific oxide-based solid electrolyte and preparing the electrolyte layer or electrode layer as a slurry.
[0006] Patent document 3 discloses a method of mixing sulfur-based solid ion conductor inorganic particles with a tetrafluoroethylene (TFE) polymer, forming a paste, and then manufacturing a film by calendering or extrusion. Prior art literature
[0007] Japanese Patent Publication No. 2017-517862, Japanese Patent Publication No. 2015-153588, International Publication No. 2021-043493 The problem to be solved
[0008] The present disclosure aims to provide a composite for a secondary battery having good properties, a composite sheet for a secondary battery containing said composite, and a secondary battery using said composite sheet.
[0009] In addition, the present disclosure aims to provide a method for manufacturing a composite sheet for a secondary battery containing a binder having a fine fiber structure. means of solving the problem
[0010] The present disclosure is a composite for a secondary battery comprising a solid electrolyte and / or an electrode active material and a binder, and
[0011] The binder is a fibril-like resin having a fibrous structure with a fibril diameter (median value) of 100 nm or less, and is included in the secondary battery composite in an amount of 0.3 mass% or more and 8 mass% or less.
[0012] It is preferable that the above fibril resin is a polytetrafluoroethylene resin.
[0013] The above composite for a secondary battery is a composite for a secondary battery obtained using a raw material composition containing a solid electrolyte and / or an electrode active material and a binder, and
[0014] It is preferable that the binder in the above raw material composition is a powdered fibril resin.
[0015] The above-mentioned powdered fibril resin preferably has a moisture content of 500 ppm or less.
[0016] It is preferable that the above-mentioned powdered fibril resin is a powdered polytetrafluoroethylene resin.
[0017] The above powdered polytetrafluoroethylene resin preferably has a standard specific gravity of 2.12 to 2.20.
[0018] The above powdered polytetrafluoroethylene resin preferably contains at least 80 mass% of polytetrafluoroethylene resin having a secondary particle size of 450 μm or more.
[0019] The above-mentioned composite for secondary batteries is preferably for solid secondary batteries.
[0020] The present disclosure is also a composite sheet for a secondary battery comprising the above-mentioned composite for a secondary battery.
[0021] The present disclosure is also an electrode comprising a composite sheet for a secondary battery comprising the above-mentioned composite for a secondary battery.
[0022] The present disclosure comprises a solid electrolyte and / or an electrode active material, and a binder, and
[0023] A method for manufacturing a composite sheet for a secondary battery, wherein the binder is a fibrilic resin having a fibrous structure with a fibril diameter (median value) of 100 nm or less, and is included in the composite for a secondary battery in an amount of 0.3 mass% or more and 8 mass% or less.
[0024] Process (a): a step of mixing a solid electrolyte and / or electrode active material, and a binder to form a composite for a secondary battery, and,
[0025] Process (b): Step of manufacturing a sheet by calendering or extruding a composite material for a secondary battery.
[0026] Includes,
[0027] The mixing of process (a) is,
[0028] (a1) a process of homogenizing a solid electrolyte and / or electrode active material, and a binder into a powder, and
[0029] (a2) A process of preparing a composite for a secondary battery by mixing the powdered raw material composition obtained by process (a1).
[0030] It is also a method for manufacturing a sheet for a secondary battery characterized by including
[0031] It is preferable that homogenization in the above process (a1) be performed at a temperature of 19°C or lower, and mixing in the process (a2) be performed at a temperature of 30°C or higher.
[0032] The above process (b) is preferably performed by calendering or extrusion at a temperature of 30 to 150°C.
[0033] In the above process (a), mixing is preferably performed while applying shear force.
[0034] The present disclosure is also a secondary battery having the composite sheet for the secondary battery. Effects of the invention
[0035] In the present disclosure, a composite for a secondary battery having good properties, a composite sheet for a secondary battery containing said composite, and a secondary battery using said composite sheet for a secondary battery can be provided. Specific details for implementing the invention
[0036] The present disclosure will be described in detail below.
[0037] The present disclosure provides a composite for a secondary battery that can be suitably used in a secondary battery, and a composite sheet containing the same.
[0038] In the composite for secondary batteries and the composite sheet containing the same disclosed in the present disclosure, a fibrillary resin such as polytetrafluoroethylene resin (PTFE) is used as a binder. In conventional composites for secondary batteries, a method of producing a composite for secondary batteries was generally used by using a solvent-soluble resin such as a copolymer of vinylidene fluoride and hexafluoropropylene as a binder and by coating and drying a slurry containing the same.
[0039] Meanwhile, it is known that, for example, when shear stress is applied to PTFE in a particulate state, it easily fibrillates. By utilizing this fibrillating property, PTFE can be used as a binder. That is, the fibrillated PTFE binds the powder components by interlocking with other powder components, and thereby can act as a binder when molding the powder components.
[0040] However, even when used as a fibrillated binder, if the fibrillation is insufficient, it cannot exhibit good performance when used as a composite for secondary batteries. In the present disclosure, this point is examined, and by performing fine fibrillation processing so that the fibrillable resin has a fibrous structure with a fibrillation diameter (median value) of 100 nm or less, the fibrillated binder can exhibit good performance as a binder for a composite for secondary batteries.
[0041] The present disclosure was completed by discovering that, in obtaining a composite for a secondary battery, a fibrillic resin is used as a binder and has a fine fiber structure, thereby enabling the acquisition of a composite for a secondary battery having good properties and a composite sheet containing the same.
[0042] In addition, the present disclosure can improve battery performance by reducing the content of the binder in the composite for secondary batteries, thereby enabling the acquisition of an electrode containing more active material or conductive aid.
[0043] The composite for secondary batteries disclosed herein is obtained by using a raw material composition containing a binder, and the binder is preferably a powdered fibrillic resin. Since a powdered binder is used as a raw material rather than a binder-containing dispersion, the problem of solvent selectivity is eliminated. Furthermore, since a dispersion is not used, there is little moisture derived from the raw materials in the composite for secondary batteries, so problems caused by the mixing of moisture are not caused. Consequently, it is possible to produce a battery with excellent ion conductivity, which has the advantage of improving battery performance.
[0044] The composite for secondary batteries of the present disclosure comprises a binder having a fibrous structure as a component when used as a composite for secondary batteries. Furthermore, in the present disclosure, it is important that the fibril diameter (median value) of the binder is 100 nm or less. The objective of the present disclosure is achieved by the presence of a binder with such a fine fibril diameter in the composite for secondary batteries, which acts to bind the powders of the components constituting the composite for secondary batteries together.
[0045] The above fibril diameter (median value) is a value measured by the following method.
[0046] (1) Using a scanning electron microscope (S-4800 model, manufactured by Hitachi Seisakusho Co., Ltd.), a magnified photograph (7000x) of the composite sheet for secondary batteries is taken and an image is obtained.
[0047] (2) Divide the image into three equal parts by drawing two lines horizontally at equal intervals.
[0048] (3) For all fibrillated binders on the straight line above, the diameter of each fibrillated binder is measured at three locations, and the average value is taken as the diameter of the fibrillated binder. The three locations to be measured are the intersection point between the fibrillated binder and the straight line, and locations offset by 0.5 μm upward and downward from each intersection point (excluding primary particles of the non-fiberized binder).
[0049] (4) The above operation of (3) is performed on all fibrillated binders on the straight line below.
[0050] (5) Move 1 mm to the right of the screen starting from the first image and take another picture to measure the diameter of the fibrillated binder according to (3) and (4). Repeat this process, and stop when the number of measurements exceeds 80.
[0051] (6) The median diameter of all fibrillated binders measured above was taken as the size of the fibrillation diameter.
[0052] The above fibril diameter (median) is preferably 100 nm or less, more preferably 85 nm or less, and even more preferably 70 nm or less. Additionally, if fibrillation is performed excessively, flexibility tends to be lost. Although the lower limit is not specifically limited, from the perspective of strength, it is preferably 15 nm or more, more preferably 20 nm or more, and particularly preferably 31 nm or more.
[0053] The method for obtaining a binder having the above fibril diameter (median value) is not particularly limited, but for example,
[0054] A process of applying shear force while mixing a raw material composition comprising a solid electrolyte and / or electrode active material and a binder powder (1)
[0055] A process (2) for forming a composite material for a secondary battery obtained by the above process (1) into a bulk form and
[0056] A method can be performed by rolling the bulk composite for secondary batteries obtained by the above process (2) into a sheet by process (3).
[0057] In this method, for example, in process (1), by making the mixing conditions of the raw material composition 15000 rpm or less, the fibrillation of the binder can be carried out while maintaining flexibility, and by controlling the applied shear stress, the fibrill diameter (median value) of the binder can be made 100 nm or less.
[0058] In addition, it is also desirable to have a process (4) in which, after process (3), a greater load is applied to the obtained rolled sheet to roll it into a thinner sheet. It is also desirable to repeat process (4).
[0059] In addition, the fibril diameter can be adjusted by having a process (5) in which, after process (3) or process (4), the obtained rolled sheet is crushed, then formed back into a bulk form, and rolled into a sheet form. It is preferable to repeat process (5) at least once and no more than 12 times.
[0060] That is, by applying shear force, the binder powder is fibrillated, and by intertwining with powder components such as active material and solid electrolyte, a composite material for a secondary battery can be manufactured. Furthermore, the manufacturing method will be described later.
[0061] Furthermore, the term "binding agent powder" refers to a solid state as a powder, rather than a dispersed state mixed with a liquid medium. By utilizing such a state and using a binding agent in a state where no liquid medium is present, the objective of the present disclosure can be suitably achieved.
[0062] In the present disclosure, for a composite for a secondary battery containing an electrolyte, an active material is an essential component, and for a composite for a solid secondary battery, a solid electrolyte is an essential component. Additionally, when used as an electrode, a conductivity aid may be used as needed.
[0063] The powder-shaped fibril resin used as a raw material for manufacturing the composite for secondary batteries of the present disclosure preferably has a moisture content of 500 ppm or less.
[0064] It is desirable that the moisture content is 500 ppm or less, as this reduces the deterioration of the solid electrolyte when using the solid electrolyte as a powder component.
[0065] It is more preferable that the above moisture content be 300 ppm or less.
[0066] In the present disclosure, the content of the binder must be 0.3 mass% or more and 8 mass% or less in the composite for secondary batteries.
[0067] The lower limit of the binder content is preferably 0.4 mass% or more, and more preferably 0.5 mass% or more. The upper limit of the binder content is preferably 7 mass% or less, more preferably 6 mass% or less, even more preferably 4 mass% or less, even more preferably 1.7 mass% or less, and most preferably 1.0 mass% or less.
[0068] When the total of the powder components and the binder is 100 mass%, the lower limit of the binder content is preferably 0.3 mass% or more, more preferably 0.4 mass% or more, and particularly preferably 0.5 mass% or more. The upper limit is preferably 8 mass% or less, more preferably 7 mass% or less, particularly preferably 6 mass% or less, even more preferably 4 mass% or less, even more preferably 1.7 mass% or less, and most preferably 1.0 mass% or less.
[0069] In the present disclosure, by setting the content of the binder to the above range, it is possible to maintain the strength of the composite sheet for secondary batteries well while ensuring excellent battery performance.
[0070] In the present disclosure, the fibrillable resin refers to a resin that easily fibrillates when shear stress is applied. By using such a fibrillable resin as a binder, the fibrillated resin intertwines with other powder components, thereby binding the powder components and acting as a binder when molding the powder components. Examples of fibrillable resins include liquid crystal polymer (LCP), cellulose, acrylic resin, ultra-high molecular weight polyethylene, PTFE, etc., and among these, PTFE is suitable in terms of chemical stability, thermal stability, and processability.
[0071] In the present disclosure, the PTFE is not particularly limited and may be a homopolymer or a copolymer capable of fibrillation.
[0072] In the case of copolymers, fluorine atom-containing monomers that serve as comonomers include chlorotrifluoroethylene, hexafluoropropylene, fluoroalkylethylene, perfluoroalkylethylene, fluoroalkyl-fluorovinyl ether, etc.
[0073] It is preferable that the PTFE in powder form has a standard specific gravity of 2.12 to 2.20. Having a standard specific gravity within this range offers an advantage in that it allows for the production of electrode composite sheets with high strength. It is more preferable that the lower limit of the standard specific gravity be 2.13 or higher. It is more preferable that the upper limit of the standard specific gravity be 2.19 or lower, and even more preferable that it be 2.18 or lower.
[0074] Standard Specific Gravity [SSG] is determined by preparing a sample in accordance with ASTM D-4895-89 and measuring the specific gravity of the obtained sample by the water displacement method.
[0075] The above powdered PTFE preferably contains 50 mass% or more of a polytetrafluoroethylene resin having a secondary particle size of 450 μm or more, and more preferably contains 80 mass% or more. Since the PTFE having a secondary particle size of 450 μm or more is within this range, it has the advantage of being able to produce a composite sheet with high strength.
[0076] By using PTFE with a secondary particle size of 450㎛ or more, a composite sheet with lower resistance and high toughness can be obtained.
[0077] The lower limit of the average secondary particle size of the above powdered PTFE is more preferably 450 μm, and even more preferably 500 μm. The upper limit of the above secondary particle size is more preferably 700 μm or less, and even more preferably 600 μm or less. The secondary particle size can be determined, for example, by a sieve classification method.
[0078] The above powdered PTFE preferably has an average primary particle size of 150 nm or more, in order to obtain an electrode composite sheet with higher strength and excellent homogeneity. More preferably, it is 180 nm or more, even more preferably 210 nm or more, and particularly preferably 220 nm or more.
[0079] The larger the average primary particle size of PTFE, the more the increase in extrusion pressure is suppressed and the moldability is excellent when extrusion molding is performed using the powder. The upper limit is not specifically limited, but 500 nm is acceptable. From the perspective of productivity in the polymerization process, the upper limit is preferably 350 nm.
[0080] The above average primary particle size can be determined by using an aqueous dispersion of PTFE obtained by polymerization, adjusting the polymer concentration to 0.22 mass%, creating a calibration curve for the average primary particle size determined by measuring the transmittance of 550 nm of projected light per unit length of the aqueous dispersion and the positive diameter in a transmission electron microscope image, measuring the transmittance for the aqueous dispersion to be measured, and determining the value based on the calibration curve.
[0081] The PTFE used in the present disclosure may have a core-shell structure. Examples of PTFE having a core-shell structure include polytetrafluoroethylene comprising a high molecular weight polytetrafluoroethylene core and a shell of lower molecular weight polytetrafluoroethylene or modified polytetrafluoroethylene within the particles. Examples of such modified polytetrafluoroethylene include, for instance, the polytetrafluoroethylene described in Japanese Patent Publication No. 2005-527652.
[0082] PTFE in powder form satisfying each of the parameters described above can be obtained by conventional manufacturing methods. For example, it may be manufactured according to the manufacturing methods described in International Publication No. 2015-080291 or International Publication No. 2012-086710, etc.
[0083] The composite for secondary batteries disclosed herein may be used for electrodes for solid-state batteries or for electrodes for batteries containing an electrolyte. Furthermore, it may be used in a solid electrolyte layer of a solid-state battery. Depending on the application, the components constituting the composite are combined, and the object of the present disclosure is achieved by generating fibrillation that satisfies the parameters described above.
[0084] In the case where the electrode is for a solid-state battery, the composite for the secondary battery further contains an electrode active material and a solid electrolyte; in the case where the electrode is for a battery containing an electrolyte, it contains an electrode active material. If necessary, it may also contain a conductivity aid and other components. Below, each component for constituting the electrode will be described in detail.
[0085] (Electrode active material)
[0086] When the composite sheet for a secondary battery disclosed in this disclosure is used as a positive electrode sheet, a positive electrode active material is incorporated into the composite sheet for the secondary battery. The positive electrode active material may be a positive electrode active material known as a positive electrode active material for a solid-state battery. In particular, it is preferable to use a positive electrode active material capable of absorbing and releasing lithium ions.
[0087] The above positive electrode active material is not particularly limited as long as it is capable of electrochemically absorbing and releasing alkali metal ions, but, for example, a material containing an alkali metal and at least one transition metal is preferred. Specific examples include alkali metal-containing transition metal composite oxides, alkali metal-containing transition metal phosphate compounds, conductive polymers, etc.
[0088] Among these, as a positive electrode active material, an alkali metal-containing transition metal composite oxide that generates particularly high voltage is preferred. Examples of the alkali metal ions include lithium ions, sodium ions, potassium ions, etc. In a preferred embodiment, the alkali metal ion may be a lithium ion. That is, in this embodiment, the alkali metal ion secondary battery is a lithium ion secondary battery.
[0089] As the above alkali metal-containing transition metal complex oxide, for example
[0090] Formula: M a Mn 2-b M 1 b O4
[0091] (wherein M is at least one metal selected from the group consisting of Li, Na, and K; 0.9≤a; 0≤b≤1.5; M 1 Alkali metal-manganese spinel composite oxide represented by at least one metal selected from the group consisting of Fe, Co, Ni, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si, and Ge,
[0092] Formula: MNi 1-c M 2 c O2
[0093] (wherein M is at least one metal selected from the group consisting of Li, Na, and K; 0≤c≤0.5; M 2 is an alkali metal-nickel complex oxide represented by at least one metal selected from the group consisting of Fe, Co, Mn, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si, and Ge, or
[0094] Formula: MCo 1-d M 3 d O2
[0095] (wherein M is at least one metal selected from the group consisting of Li, Na, and K; 0≤d≤0.5; M 3 (at least one metal selected from the group consisting of Fe, Ni, Mn, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si, and Ge)
[0096] Examples include alkali metal-cobalt complex oxides represented by . In the above, M is preferably one metal selected from the group consisting of Li, Na, and K, more preferably Li or Na, and even more preferably Li.
[0097] Among them, MCoO2, MMnO2, MNiO2, MMn2O4, and MNi are capable of providing high-energy density and high-output secondary batteries. 0.8 Co 0.15 Al 0.05 O2, or MNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, etc. is preferred, and it is preferred to be a compound represented by the following general formula (3).
[0098]
[0099] (In the formula, M is at least one metal selected from the group consisting of Li, Na, and K, and M 5 represents at least one selected from the group consisting of Fe, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si, and Ge, and (h+i+j+k)=1.0, 0≤h≤1.0, 0≤i≤1.0, 0≤j≤1.5, 0≤k≤0.2)
[0100] As the above alkali metal-containing transition metal phosphate compound, for example, the following formula (4)
[0101]
[0102] (In the formula, M is at least one metal selected from the group consisting of Li, Na, and K, and M 4 represents at least one selected from the group consisting of V, Ti, Cr, Mn, Fe, Co, Ni, and Cu, and may be an example of a compound represented by 0.5≤e≤3, 1≤f≤2, and 1≤g≤3. In the above, M is preferably one metal selected from the group consisting of Li, Na, and K, more preferably Li or Na, and even more preferably Li.
[0103] As the transition metal of the lithium-containing transition metal phosphate compound, V, Ti, Cr, Mn, Fe, Co, Ni, Cu, etc. are preferred. Specific examples include iron phosphates such as LiFePO4, Li3Fe2(PO4)3, LiFeP2O7, cobalt phosphates such as LiCoPO4, and those in which some of the transition metal atoms that form the main component of these lithium transition metal phosphate compounds are substituted with other elements such as Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Nb, Si, etc.
[0104] As for the above lithium-containing transition metal phosphate compound, it is preferable to have an olivine-type structure.
[0105] Other positive electrode active materials include MFePO4 and MNi 0.8 Co 0.2 O2, M 1.2 Fe 0.4 Mn 0.4 O2, MNi 0.5 Mn 1.5 Examples include O2, MV3O6, M2MnO3 (wherein M is at least one metal selected from the group consisting of Li, Na, and K). In particular, M2MnO3, MNi 0.5 Mn 1.5Positive electrode active materials such as O2 are desirable in that their crystal structure does not collapse when the secondary battery is operated at a voltage exceeding 4.4V or 4.6V or higher. Therefore, an electrochemical device such as a secondary battery using a positive electrode material including the positive electrode active material exemplified above is desirable in that, even when stored at high temperatures, the remaining capacity is unlikely to decrease and the resistance increase rate is unlikely to change, and the battery performance is not degraded even when operated at high voltage.
[0106] Other positive electrode active materials include M2MnO3 and MM 6 O2(wherein M is at least one metal selected from the group consisting of Li, Na, and K, and M 6 Solid solution materials of transition metals such as silver, Co, Ni, Mn, and Fe can also be cited.
[0107] As the above solid solution material, for example, the general formula Mx[Mn (1-y) M 7 y ]O z It is an alkali metal manganese oxide represented by . Here, M in the formula is at least one metal selected from the group consisting of Li, Na, and K, and M 7 It consists of at least one metallic element other than silver, M, and Mn, and includes one or more elements selected from the group consisting of, for example, Co, Ni, Fe, Ti, Mo, W, Cr, Zr, and Sn. In addition, the values of x, y, and z in the formula are 1 <x<2, 0≤y<1, 1.5<z<3의 범위이다. 그 중에서도, Li 1.2 Mn 0.5 Co 0.14 Ni 0.14 Manganese-containing solid solution materials that incorporate LiNiO2 or LiCoO2 based on Li2MnO3, such as O2, are desirable in that they can provide alkali metal ion secondary batteries with high energy density.
[0108] In addition, it is desirable to include lithium phosphate in the positive electrode active material as this improves continuous charging characteristics. Although there are no restrictions on the use of lithium phosphate, it is preferable to use a mixture of the above-mentioned positive electrode active material and lithium phosphate. The amount of lithium phosphate used is preferably 0.1 mass% or more, more preferably 0.3 mass% or more, and even more preferably 0.5 mass% or more with respect to the total of the above-mentioned positive electrode active material and lithium phosphate, and is preferably 10 mass% or less, more preferably 8 mass% or less, and even more preferably 5 mass% or less.
[0109] Examples of the above conductive polymers include p-doped conductive polymers and n-doped conductive polymers. Examples of conductive polymers include polyacetylene-based, polyphenylene-based, heterocyclic polymers, ionic polymers, ladder and network polymers, etc.
[0110] Among the above positive electrode active materials, nickel-containing positive electrode active materials are suitable. By including nickel, the active material can be increased in capacity, thereby improving battery performance. Furthermore, since the amount of cobalt, a rare metal, can be reduced, it offers an advantage in terms of cost.
[0111] In particular, it is desirable to contain a lithium-nickel-based composite oxide.
[0112] As a lithium-nickel-based composite oxide, general formula (1): Li y Ni 1-x M x O2
[0113] A lithium-nickel composite oxide represented by (wherein x is 0.01≤x≤0.5, y is 0.9≤y≤1.2, and M represents a metal atom (excluding Ni)) is preferred. A positive electrode active material containing a large amount of Ni in this way is beneficial for increasing the capacity of a secondary battery.
[0114] In general formula (1), x is a coefficient satisfying 0.01≤x≤0.5, and is preferably 0.05≤x≤0.4 and more preferably 0.10≤x≤0.3 in order to obtain a higher capacity secondary battery.
[0115] In general formula (1), the metal atoms of M may include V, Ti, Cr, Mn, Fe, Co, Cu, Al, Zn, Mg, Ga, Zr, Si, etc. As for the metal atoms of M, transition metals such as V, Ti, Cr, Mn, Fe, Co, Cu, etc., or a combination of the above transition metals and other metals such as Al, Ti, V, Cr, Mn, Fe, Co, Cu, Zn, Mg, Ga, Zr, Si is preferred.
[0116] As a lithium-nickel-based composite oxide, LiNi 0.82 Co 0.15 Al 0.03 O2, LiNi 0.6 Mn 0.2 Co 0.2 O2 and LiNi 0.8 Mn 0.1 Co 0.1 At least one type selected from the group consisting of O2 is preferred, and LiNi 0.82 Co 0.15 Al 0.03 O2 and LiNi 0.8 Mn 0.1 Co 0.1 At least one type selected from the group consisting of O2 is more preferable.
[0117] In addition to the lithium-nickel composite oxide represented by general formula (1), a different positive electrode active material may be used in combination. Specifically, as different positive electrode active materials, LiCoO2, LiMnO2, LiMn2O4, Li2MnO3, and LiMn 1.8 Al 0.2 O4, Li4Ti5O 12 , LiFePO4, Li3Fe2(PO4)3, LiFeP2O7, LiCoPO4, Li 1.2 Fe 0.4Mn 0.4 O2, LiNiO2, LiNi 0.5 Mn 0.3 Co 0.2 Examples include O2.
[0118] In addition, a material having a different composition may be attached to the surface of the above positive electrode active material. Examples of surface-attached materials include oxides such as aluminum oxide, silicon oxide, titanium oxide, zirconium oxide, magnesium oxide, calcium oxide, boron oxide, antimony oxide, and bismuth oxide; sulfates such as lithium sulfate, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate, and aluminum sulfate; carbonates such as lithium carbonate, calcium carbonate, and magnesium carbonate; and carbon.
[0119] These surface-attaching materials can be attached to the surface of a positive electrode active material by methods such as dissolving or suspending them in a solvent and impregnating them into the corresponding positive electrode active material, or adding them and then drying; by dissolving or suspending a surface-attaching material precursor in a solvent and adding it to the corresponding positive electrode active material, followed by a reaction through heating, etc.; or by adding it to a positive electrode active material precursor and simultaneously calcining it. In addition, when carbon is attached, a method of mechanically attaching carbonaceous material in the form of, for example, activated carbon, later may also be utilized.
[0120] As for the amount of the surface-attached material, in terms of mass relative to the positive electrode active material, it is used in a lower limit preferably at least 0.1 ppm, more preferably at least 1 ppm, and even more preferably at least 10 ppm, and in an upper limit preferably at least 20%, more preferably at least 10%, and even more preferably at least 5%. By means of the surface-attached material, the oxidation reaction of the solid electrolyte on the surface of the positive electrode active material can be suppressed, thereby improving battery life. If the amount of attachment is excessively small, the effect is not sufficiently manifested, and if it is excessively large, resistance may increase in order to hinder the entry and exit of lithium ions.
[0121] Examples of particle shapes of the positive electrode active material include conventionally used bulk, polyhedral, spherical, elliptical, plate-like, needle-like, and columnar shapes. Additionally, primary particles may aggregate to form secondary particles.
[0122] The tap density of the positive electrode active material is preferably 0.5 g / cm³ or higher, more preferably 0.8 g / cm³ or higher, and even more preferably 1.0 g / cm³ or higher. If the tap density of the positive electrode active material falls below the above lower limit, the amount of dispersion medium required during the formation of the positive electrode active material layer increases, along with the required amount of conductive material or binder, and the filling rate of the positive electrode active material in the positive electrode active material layer is restricted, which may result in a limitation of the battery capacity. By using a composite oxide powder with a high tap density, a high-density positive electrode active material layer can be formed. Generally, a higher tap density is preferable, and there is no particular upper limit; however, if it is excessively high, the diffusion of lithium ions using the solid electrolyte as a medium within the positive electrode active material layer becomes rate-limited, and load characteristics may easily deteriorate; therefore, the upper limit is preferably 4.0 g / cm³ or lower, more preferably 3.7 g / cm³ or lower, and even more preferably 3.5 g / cm³ or lower.
[0123] In addition, in the present disclosure, the tap density is determined as the powder packing density (tap density) g / cm³ when 5 to 10 g of positive electrode active material powder is placed in a 10 ml glass graduated cylinder and tapped 200 times with a stroke of about 20 mm.
[0124] The particle median diameter d50 of the positive electrode active material (the secondary particle diameter in cases where primary particles aggregate to form secondary particles) is preferably 0.3 μm or more, more preferably 0.5 μm or more, even more preferably 0.8 μm or more, and most preferably 1.0 μm or more, and is also preferably 30 μm or less, more preferably 27 μm or less, even more preferably 25 μm or less, and most preferably 22 μm or less. If it falls below the lower limit, it may not be possible to obtain a high-tap density product, and if it exceeds the upper limit, it may cause a decrease in battery performance because lithium diffusion within the particles takes time, or problems such as streaks may occur when manufacturing the positive electrode of the battery, that is, when slurrying the active material with a conductive material or binder with a solvent and applying it as a thin film. Here, by mixing two or more types of the positive electrode active materials having different median diameters d50, the chargeability during the manufacturing of the positive electrode can be further improved.
[0125] In addition, in the present disclosure, the median diameter d50 is measured by a known laser diffraction / scattering particle size distribution measuring device. When using HORIBA LA-920 as the particle size distribution meter, a 0.1 mass% aqueous sodium hexametaphosphate solution is used as the dispersion medium during measurement, and the measurement is performed by setting the refractive index to 1.24 after 5 minutes of ultrasonic dispersion.
[0126] In cases where primary particles aggregate to form secondary particles, the average primary particle size of the positive electrode active material is preferably 0.05 μm or more, more preferably 0.1 μm or more, and even more preferably 0.2 μm or more, and the upper limit is preferably 5 μm or less, more preferably 4 μm or less, even more preferably 3 μm or less, and most preferably 2 μm or less. If the upper limit is exceeded, it is difficult to form spherical secondary particles, and the powder filling ability is adversely affected or the specific surface area is significantly reduced, so there is a high possibility that battery performance, such as output characteristics, will be degraded. Conversely, if the lower limit is lowered, problems such as reduced reversibility of charge and discharge may occur because crystals are not developed properly.
[0127] In addition, in the present disclosure, the average primary particle size of the positive electrode active material is measured by observation using a scanning electron microscope (SEM). Specifically, in a photograph at a magnification of 10,000 times, the longest value of the intercept by the left and right boundary lines of the primary particles with respect to a straight line in the horizontal direction is obtained for any 50 primary particles, and the average value is taken.
[0128] The BET specific surface area of the positive electrode active material is preferably 0.1 m² / g or more, more preferably 0.2 m² / g or more, and even more preferably 0.3 m² / g or more, and the upper limit is preferably 50 m² / g or less, more preferably 40 m² / g or less, and even more preferably 30 m² / g or less. If the BET specific surface area is smaller than this range, battery performance is likely to degrade, and if it is larger, it becomes difficult to increase the tap density, which may cause problems with coating properties when forming the positive electrode active material layer.
[0129] In addition, in the present disclosure, the BET specific surface area is defined as a value measured by the nitrogen adsorption BET 1-point method by the gas flow method, using a surface area meter (e.g., an automatic surface area measuring device manufactured by Okura Riken), pre-drying the sample at 150°C for 30 minutes under nitrogen flow, and then using a nitrogen-helium mixed gas that is accurately adjusted so that the relative pressure of nitrogen with respect to atmospheric pressure is 0.3.
[0130] When the secondary battery of the present disclosure is used as a large lithium-ion secondary battery for hybrid vehicles or distributed power sources, high output is required, so it is preferable that the particles of the positive electrode active material consist mainly of secondary particles.
[0131] It is preferable that the particles of the positive electrode active material contain 0.5 to 7.0 volume% of fine particles having an average particle size of secondary particles of 40 μm or less and an average primary particle size of 1 μm or less. By including fine particles with an average primary particle size of 1 μm or less, the contact area with the solid electrolyte is increased, and the diffusion of lithium ions between the sheet for the all-solid-state secondary battery and the solid electrolyte can be accelerated, thereby improving the output performance of the battery.
[0132] As a method for manufacturing positive electrode active materials, general methods for manufacturing inorganic compounds are utilized. In particular, various methods are considered to produce spherical or elliptical active materials; examples include a method in which a transition metal raw material is dissolved or ground and dispersed in a solvent such as water, a spherical precursor is prepared and recovered by adjusting the pH while stirring, and then, if necessary, dried and calcined at a high temperature with the addition of a Li source such as LiOH, Li2CO3, or LiNO3 to obtain the active material.
[0133] For the manufacture of the positive electrode, the above-described positive electrode active material may be used alone, or two or more materials of different compositions may be used in combination or in any ratio. In this case, a preferred combination is LiCoO2 and LiNi 0.33 Co 0.33 Mn 0.33 Examples include combinations of ternary systems such as O2, combinations of LiCoO2 and LiMn2O4 or in which part of this Mn is substituted with other transition metals, or combinations of LiFePO4 and LiCoO2 or in which part of this Co is substituted with other transition metals.
[0134] The content of the above positive electrode active material is preferably 50 to 99.5 mass% in the positive electrode composite, more preferably 60 to 99 mass%, and more preferably 69 to 96.7 mass%, in terms of high battery capacity.
[0135] In addition, the content of the positive electrode active material is preferably 80 mass% or more, more preferably 82 mass% or more, and particularly preferably 84 mass% or more. In addition, the upper limit is preferably 99 mass% or less, and more preferably 98 mass% or less. If the content of the positive electrode active material in the positive electrode composite is low, the electrical capacitance may become insufficient. Conversely, if the content is too high, the electron-ion conductivity or strength of the positive electrode may be insufficient.
[0136] When the composite sheet for a secondary battery of the present disclosure is used as a negative electrode sheet, a negative electrode active material is incorporated into the composite sheet for the secondary battery.
[0137] The above negative electrode active material is not particularly limited and includes, for example, carbonaceous materials such as lithium metal, artificial graphite, graphite carbon fiber, resin calcined carbon, pyrolytic vapor-grown carbon, coke, mesocarbon micro beads (MCMB), furfuryl alcohol resin calcined carbon, polyacene, pitch-based carbon fiber, vapor-grown carbon fiber, natural graphite, and non-graphitizable carbon, silicon-containing compounds such as silicon and silicon alloys, and Li4Ti5O12 Examples include any of the above, or a mixture of two or more types. Among these, a carbonaceous material containing at least a part of it, or a silicon-containing compound can be particularly suitablely used.
[0138] The content of the above negative electrode active material is preferably 50 to 99.5 mass% in the negative electrode composite, more preferably 60 to 99 mass%, and more preferably 69 to 96.7 mass%, in terms of high battery capacity.
[0139] In addition, the content of the negative electrode active material is preferably 80 mass% or more, more preferably 82 mass% or more, and particularly preferably 84 mass% or more. In addition, the upper limit is preferably 99 mass% or less, and more preferably 98 mass% or less. If the content of the negative electrode active material in the negative electrode composite is low, the electrical capacitance may become insufficient. Conversely, if the content is too high, the electron-ion conductivity or strength of the negative electrode may be insufficient.
[0140] (Solid electrolyte)
[0141] The solid electrolyte used in the composite for secondary batteries of the present disclosure may be a sulfide-based solid electrolyte or an oxide-based solid electrolyte. In particular, when a sulfide-based solid electrolyte is used, there is an advantage of flexibility.
[0142] As a sulfide-based solid electrolyte, for example, a lithium ion-conducting inorganic solid electrolyte that satisfies the composition represented by the following formula (1) can be cited.
[0143]
[0144] In the formula, M represents an element selected from B, Zn, Sn, Si, Cu, Ga, Sb, Al, and Ge. A represents an element selected from I, Br, Cl, and F. a1 to e1 represent the compositional ratio of each element, and a1:b1:c1:d1:e1 satisfies 1 to 12:0 to 5:1:2 to 12:0 to 10. a1 is preferably 1 to 9, and more preferably 1.5 to 7.5. b1 is preferably 0 to 3, and more preferably 0 to 1. d1 is preferably 2.5 to 10, and more preferably 3.0 to 8.5. e1 is preferably 0 to 5, and more preferably 0 to 3.
[0145] In the present disclosure, the sulfide-based solid electrolyte preferably contains lithium. The lithium-containing sulfide-based solid electrolyte is used in solid-state batteries that use lithium ions as carriers and is particularly preferred in that it is an electrochemical device having high energy density.
[0146] The compositional ratio of each element can be controlled by adjusting the amount of raw material compounds used when manufacturing a sulfide-based inorganic solid electrolyte, as follows.
[0147] Sulfide-based inorganic solid electrolytes may be amorphous (glass), crystallized (glass ceramic), or only partially crystallized. For example, Li-PS-based glass containing Li, P, and S, or Li-PS-based glass ceramics containing Li, P, and S may be used.
[0148] Sulfide-based inorganic solid electrolytes can be prepared by the reaction of at least two raw materials selected from, for example, lithium sulfide (Li2S), phosphorus sulfide (e.g., phosphorus pentasulfide (P2S5)), elemental phosphorus, elemental sulfur, sodium sulfide, hydrogen sulfide, lithium halide (e.g., LiI, LiBr, LiCl), and sulfides of the element represented by M (e.g., SiS2, SnS, GeS2).
[0149] As a specific example of a sulfide-based inorganic solid electrolyte, an example of a combination of raw materials is shown below. For example, Li2S-P2S5-LiCl, Li2S-P2S5-H2S, Li2S-P2S5-H2S-LiCl, Li2S-LiI-P2S5, Li2S-LiI-Li2O-P2S5, Li2S-LiBr-P2S5, Li2S-Li2O-P2S5, Li2S-Li3PO4-P2S5, Li2S-P2S5-P2O5, Li2S-P2S5-SiS2, Li2S-P2S5-SiS2-LiCl, Li2S-P2S5-SnS, Li2S-P2S5-Al2S3, Li2S-GeS2, Li2S-GeS2-ZnS, Li2S-Ga2S3, Li2S-GeS2-Ga2S3, Li2S-GeS2-P2S5, Li2S-GeS2-Sb2S5, Li2S-GeS2-Al2S3, Li2S-SiS2, Li2S-Al2S3, Li2S-SiS2-Al2S3, Li2S-SiS2-P2S5, Li2S-SiS2-P2S5-LiI, Li2S-SiS2-LiI, Li2S-SiS2-Li4SiO4, Li2S-SiS2-Li3PO4, Li 10 GeP2S 12 Examples include the above. However, the mixing ratio of each ingredient is irrelevant.
[0150] In particular, it is preferable that the sulfide-based solid electrolyte be a sulfide-based solid electrolyte that satisfies the composition represented by the following formula (A).
[0151]
[0152] (where 0.6≤a≤0.86, 0≤b≤0.333, 0≤c≤0.3, 0.05≤b+c≤0.4, X1 Silver is Ge, Sn, Ti, or Si, X 2 represents Cl, Br, or I, provided that neither b nor c is 0.
[0153] As an example of a sulfide-based solid electrolyte represented by the above formula (A), specifically, 0.714Li2S-0.143SnS2-0.143P2S5(Li 10 SnP2S 12 (LSPS)), 0.625Li2S-0.25LiCl-0.125P2S5(Li6PS5Cl(LPSCl)), 0.715Li2S-0.143GeS2-0.142P2S5(Li 10 GeP2S 12 Any of the selected from (LGPS), etc., or a mixture of two or more types may be used.
[0154] The average particle size of the sulfide-based solid electrolyte is preferably 0.1 μm or more and 20 μm or less. As an upper limit, it is more preferable to be 0.2 μm or more, and even more preferable to be 0.3 μm or more. As an upper limit, it is more preferable to be 18 μm or less, and even more preferable to be 15 μm or less.
[0155] If the average particle size of the sulfide-based solid electrolyte is less than 0.1㎛, handling of the powder may become difficult. On the other hand, if the average particle size of the sulfide-based solid electrolyte exceeds 20㎛, press formability may deteriorate.
[0156] In addition, the average particle size of the sulfide-based solid electrolyte particles is measured in the following procedure.
[0157] A 1 mass% dispersion of sulfide-based solid electrolyte particles is diluted in a 20 ml sample bottle using water (or heptane in the case of substances unstable in water). The diluted dispersion sample is irradiated with 1 kHz ultrasound for 10 minutes and used for testing immediately thereafter. Using this dispersion sample, data is introduced 50 times using a laser diffraction / scattering particle size distribution measuring device LA-920 (manufactured by HORIBA) at a temperature of 25°C with a measuring quartz cell to obtain the volume-averaged particle size. For other detailed conditions, refer to the description in JIS Z8828:2013 “Particle Size Analysis - Dynamic Light Scattering Method” as necessary. Five samples are prepared per level, and the average value is adopted.
[0158] The method for adjusting the average particle size of the sulfide solid electrolyte is not particularly limited, but is performed as follows, for example. A known grinder or classifier is used. For example, a mortar, sand mill, ball mill, jet mill, or sieve is suitably used. Depending on the properties of the solid electrolyte, a solvent such as water or ethanol may be added during grinding. To achieve the desired particle size, it is desirable to perform classification. Classification is not particularly limited and can be performed using a sieve, an air classifier, etc.
[0159] The above oxide-based solid electrolyte is preferably a compound that contains oxygen atoms (O), has ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, and also has electronic insulation properties.
[0160] Oxide-based solid electrolytes have an ionic conductivity of 1×10⁻⁶ -6 It is desirable that it be S / cm or higher, and 5×10 -6 It is more desirable to have S / cm or more, and 1×10 -5 It is particularly desirable that it be S / cm or higher.
[0161] Specific examples of compounds include, for instance, Li xa La yaTiO3 [xa satisfies 0.3≤xa≤0.7 and ya satisfies 0.3≤ya≤0.7](LLT); Li xb La yb Zr zb M bb mb O nb (M bb is one or more elements selected from Al, Mg, Ca, Sr, V, Nb, Ta, Ti, Ge, In, and Sn. xb satisfies 5≤xb≤10, yb satisfies 1≤yb≤4, zb satisfies 1≤zb≤4, mb satisfies 0≤mb≤2, and nb satisfies 5≤nb≤20); Li xc B yc M cc zc O nc (M cc is one or more elements selected from C, S, Al, Si, Ga, Ge, In, and Sn. xc satisfies 0≤xc≤5, yc satisfies 0≤yc≤1, zc satisfies 0≤zc≤1, and nc satisfies 0≤nc≤6); Li xd (Al, Ga) yd (Ti, Ge) zd Si ad P md O nd (xd satisfies 1≤xd≤3, yd satisfies 0≤yd≤1, zd satisfies 0≤zd≤2, ad satisfies 0≤ad≤1, md satisfies 1≤md≤7, and nd satisfies 3≤nd≤13); Li (3-2xe) M ee xe D ee O(xe represents a number between 0 and 0.1 inclusive, and M ee represents a divalent metal atom. D ee represents a halogen atom or a combination of two or more halogen atoms); Li xf Si yf O zf (xf satisfies 1≤xf≤5, and yf is 0 <yf≤3을 충족하고, zf는 1≤zf≤10을 충족함); Lixg S yg O zg (xg satisfies 1≤xg≤3 and yg is 0 <yg≤2를 충족하고, zg는 1≤zg≤10을 충족함); Li3BO3; Li3BO3-Li2SO4, Li2O-B2O3-P2O5, Li2O-SiO2, Li6BaLa2Ta2O 12 , Li3PO (4-3 / 2w) N w (w is w<1), Li having a LISICON (Lithium superionic conductor) type crystal structure 3.5 Zn 0.25 GeO4; La having a perovskite-type crystal structure 0.55 Li 0.35 TiO3;
[0162] LiTi2P3O having a NASICON (Natrium superionic conductor) type crystal structure 12 , Li 1+xh+yh (Al, Ga) xh (Ti, Ge) 2-xh Si yh P 3-yh O 12 (xh satisfies 0≤xh≤1 and yh satisfies 0≤yh≤1); as a specific example, for example, Li 1.3 Al 0.3 Ti 1.7 Examples include (PO4)3. Li7La3Zr2O, which has a garnet-type crystal structure. 12 Examples include (LLZ).
[0163] In addition, ceramic materials in which elemental substitution has been performed on LLZ are also known. For example,
[0164] It is preferable to employ a composition comprising at least one element selected from the group consisting of Mg, Al, Si, Ca (calcium), Ti, V (vanadium), Ga (gallium), Sr, Y (yttrium), Nb (niobium), Sn (tin), Sb (antimony), Ba (barium), Hf (hafnium), Ta (tantal), W (tungsten), Bi (bismuth), and lanthanide elements. As a specific example, for instance, Li 6.25 La3Zr2Al 0.25 O 12 You can lift the back.
[0165] In addition, phosphorus compounds containing Li, P, and O are also preferred. For example, lithium phosphate (Li3PO4); LiPON and LiPOD, in which some of the oxygen in lithium phosphate is substituted with nitrogen. 1 (D 1 Examples include one or more elements preferably selected from Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zr, Nb, Mo, Ru, Ag, Ta, W, Pt, and Au.
[0166] Also, LiA 1 ON(A 1 One or more elements selected from silver, Si, B, Ge, Al, C, and Ga, etc.) can also be preferably used.
[0167] Specific examples include Li2O-Al2O3-SiO2-P2O5-TiO2-GeO2, Li2O-Al2O3-SiO2-P2O5-TiO2, etc.
[0168] The above oxide-based inorganic solid electrolyte preferably contains at least one element selected from the group consisting of Mg, Al, Si, Ca, Ti, Ga, Sr, Nb, Sn, Ba, and W. The oxide-based inorganic solid electrolyte containing these is particularly desirable in that it has good Li ion conductivity.
[0169] It is preferable that the above oxide-based solid electrolyte contains lithium. An oxide-based solid electrolyte containing lithium is used in a solid-state battery that uses lithium ions as a carrier and is particularly desirable in that it is an electrochemical device having high energy density.
[0170] The above oxide-based solid electrolyte is preferably an oxide having a crystalline structure. An oxide having a crystalline structure is particularly desirable in that it has good Li ion conductivity.
[0171] As oxides having a crystal structure, the perovskite type (La 0.51 Li 0.34 TiO 2.94 (etc.), NASICON type (Li 1.3 Al 0.3 Ti 1.7 (PO4)3rd), garnet type (Li7La3Zr2O 12 Examples include (LLZ), etc. Among them, the NASICON type is preferred.
[0172] The volume average particle size of the oxide-based solid electrolyte is not particularly limited, but it is preferably 0.01 μm or larger, and more preferably 0.03 μm or larger. As an upper limit, it is preferably 100 μm or smaller, and more preferably 50 μm or smaller.
[0173] In addition, the average particle size of oxide-based solid electrolyte particles is measured in the following procedure. A 1 mass% dispersion of oxide-based solid electrolyte particles is diluted in a 20 ml sample bottle using water (or heptane in the case of substances unstable in water). The diluted dispersion sample is irradiated with 1 kHz ultrasound for 10 minutes and used for testing immediately thereafter. Using this dispersion sample, data is introduced 50 times using a laser diffraction / scattering particle size distribution measuring device LA-920 (manufactured by HORIBA) at a temperature of 25°C with a measuring quartz cell to obtain the volume-averaged particle size. For other detailed conditions, etc., refer to the description in JIS Z8828:2013 “Particle Size Analysis - Dynamic Light Scattering Method” as necessary. Five samples are prepared per level, and their average values are adopted.
[0174] Regarding the content of the solid component in the composite for a secondary battery of a solid electrolyte, when used in a solid secondary battery, considering the reduction of interfacial resistance and the maintenance of the reduced interfacial resistance, it is preferable that the content of the electrode be 3 mass% or more, 4 mass% or more, particularly preferable that it be 5 mass% or more, and more particularly preferable that it be 10 mass% or more, based on 100 mass% of the solid component. As for the upper limit, from the same perspective, it is preferable that it be 99 mass% or less, more preferable that it be 90 mass% or less, and particularly preferable that it be 80 mass% or less.
[0175] In addition, regarding the solid electrolyte layer disposed between the positive electrode and the negative electrode, it is preferable that it be 50 mass% or more, more preferable that it be 60 mass% or more, and particularly preferable that it be 70 mass% or more. In the same regard, as for the upper limit, it is preferable that it be 99.9 mass% or less, more preferable that it be 99.8 mass% or less, and particularly preferable that it be 99.7 mass% or less.
[0176] The above solid electrolyte may be used as a single type or in combination of two or more types.
[0177] In addition, in this specification, solid content (solid component) refers to a component that does not volatilize or evaporate and disappear when a drying treatment is performed at 170°C for 6 hours under a nitrogen atmosphere.
[0178] (Challenge Supplement)
[0179] As the above-mentioned conductive aid, known conductive materials may be used at will. Specific examples include metal materials such as copper and nickel, graphite such as natural graphite and artificial graphite, carbon black such as acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal black, and carbon materials such as needle coke, carbon nanotubes, fullerene, and amorphous carbon such as VGCF. In addition, one of these may be used alone, or two or more may be used in any combination and ratio.
[0180] When a conductivity aid is used, the conductivity aid is used in a composite for a secondary battery in an amount of typically 0.01 mass% or more, preferably 0.1 mass% or more, more preferably 0.5 mass% or more, and typically 50 mass% or less, preferably 30 mass% or less, more preferably 15 mass% or less. If the content is lower than this range, the conductivity may become insufficient. Conversely, if the content is higher than this range, the battery capacity may decrease.
[0181] (Other ingredients)
[0182] The composite sheet for secondary batteries may further contain a thermoplastic resin.
[0183] Examples of thermoplastic resins include vinylidene fluoride, polypropylene, polyethylene, polystyrene, polyethylene terephthalate, polyethylene oxide, etc. One type may be used alone, or two or more types may be used in any combination and ratio.
[0184] The ratio of thermoplastic resin to the electrode active material is typically 0.01 mass% or more, preferably 0.05 mass% or more, more preferably 0.10 mass% or more, and is also typically 3.0 mass% or less, preferably 2.5 mass% or less, more preferably 2.0 mass% or less. By adding thermoplastic resin, the mechanical strength of the electrode can be improved. If this range is exceeded, the proportion of active material in the electrode composite decreases, and problems such as a decrease in battery capacity or an increase in resistance between active materials may occur.
[0185] In the composite sheet for a secondary battery of the present disclosure, the content of the binder is, as a ratio of the binder in the composite sheet for a secondary battery, typically 0.2 mass% or more, preferably 0.3 mass% or more, more preferably 0.5 mass% or more, and typically 10 mass% or less, preferably 6.0 mass% or less, more preferably 4 mass% or less, even more preferably 1.7 mass% or less, and most preferably 1.0 mass% or less. If the ratio of the binder is excessively low, the active material cannot be sufficiently retained and supported within the composite sheet for a secondary battery, resulting in insufficient mechanical strength of the composite sheet for a secondary battery and potentially deteriorating battery performance such as cycle characteristics. On the other hand, if it is too high, it may lead to a decrease in battery capacity or conductivity.
[0186] The composite for secondary batteries of the present disclosure is particularly suitable for lithium-ion solid secondary batteries.
[0187] The composite for secondary batteries disclosed in this invention is typically used in a sheet form when used in solid-state secondary batteries.
[0188] The composite sheet for a secondary battery disclosed in this disclosure may be used as a positive electrode sheet or as a negative electrode sheet. Additionally, it may be used as a solid electrolyte layer sheet.
[0189] Among these, when used as an electrode sheet, it contains active material particles. The active material particles may be a positive electrode active material or a negative electrode active material. The composite sheet for a secondary battery disclosed herein is more suitably used as a positive electrode sheet using a positive electrode active material. Furthermore, when used as an electrode sheet, it may contain a conductivity aid if necessary.
[0190] The thickness of the composite sheet for a secondary battery of the present disclosure is preferably 10 to 150 μm, and more preferably 15 to 100 μm.
[0191] (Manufacturing method)
[0192] The method for manufacturing a composite sheet for a secondary battery according to the present disclosure preferably involves using a raw material composition obtained by mixing each of the above-described components and forming it into a sheet. In the sheeting process, since a drying process can be omitted, it is preferable to reduce or not use the amount of liquid medium used, and to perform the process by applying shear stress to the raw material composition in powder form without preparing a slurry.
[0193] Although the manufacturing method of the composite sheet for secondary batteries disclosed in this disclosure is not limited, specific examples of manufacturing methods are provided below.
[0194] Process (a): a step of mixing a solid electrolyte and / or electrode active material, and a binder to form a composite for a secondary battery, and
[0195] Process (b): A step of manufacturing a sheet by calendering or extruding a composite material for a secondary battery.
[0196] Includes,
[0197] The mixing of process (a) is,
[0198] (a1) a process of homogenizing a solid electrolyte and / or electrode active material, and a binder into a powder, and
[0199] (a2) A process of preparing a composite for a secondary battery by mixing the powdered raw material composition obtained by process (a1).
[0200] It is preferable that the manufacturing method be characterized by including
[0201] For example, PTFE has two transition temperatures at approximately 19°C and 30°C. Below 19°C, PTFE can be easily mixed while maintaining its shape. However, above 19°C, the structure of the PTFE particles loosens, making it more sensitive to mechanical shear. At temperatures exceeding 30°C, a higher degree of fibrillation occurs.
[0202] For this reason, it is preferable to perform the homogenization of (a1) at a temperature of 19°C or lower, preferably from 0°C to 19°C.
[0203] That is, in such a (a1), it is desirable to mix and homogenize without causing fibrillation.
[0204] In the subsequent process (a2), mixing is preferably performed at a temperature of 30°C or higher to induce fibrillation.
[0205] The above process (a2) is preferably carried out at a temperature of 30°C to 150°C, more preferably 35°C to 120°C, and even more preferably 40°C to 80°C.
[0206] In one embodiment, the calendering or extrusion of the process (b) is carried out at a temperature between 30°C and 150°C, preferably between 35°C and 120°C, more preferably between 40°C and 100°C.
[0207] In the mixing of the above process (a), it is preferable to perform the process while applying shear force.
[0208] Specific mixing methods include mixing using a W-type mixer, V-type mixer, drum-type mixer, ribbon mixer, conical screw-type mixer, uniaxial mixer, twin-axial mixer, mixer, stirring mixer, planetary mixer, Henschel mixer, high-speed mixer, etc.
[0209] Mixing conditions can be set by appropriately adjusting the rotational speed and mixing time. For example, it is suitable to set the rotational speed to 15,000 rpm or less. Preferably, it is 10 rpm or more, more preferably 1,000 rpm or more, and even more preferably 3,000 rpm or more; further preferably, it is in the range of 12,000 rpm or less, more preferably 11,000 rpm or less, and even more preferably 10,000 rpm. If the speed falls below the above range, mixing takes time and affects productivity. In addition, if it exceeds the range, excessive fibrillation may occur, and there is a risk that the electrode composite sheet will become weak.
[0210] In process (a1), it is preferable to perform the process with a weaker shear force than in process (a2).
[0211] It is preferable that the raw material composition does not contain a liquid solvent, but a small amount of lubricant may be used in the above process (a2). That is, a paste may be prepared by adding a lubricant to the powdered raw material composition obtained by the above process (a1).
[0212] The above lubricants are not particularly limited and may include ether compounds, alcohols, ionic liquids, carbonates, aliphatic hydrocarbons (low-polarity solvents such as heptane and xylene), isoparaffinic hydrocarbon compounds, and petroleum fractions (gasoline (C4-C10), naphtha (C4-C11), kerosene / paraffin (C10-C16), and mixtures thereof).
[0213] It is preferable that the above lubricant has a moisture content of 1000 ppm or less.
[0214] It is desirable that the moisture content be 1000 ppm or less in that it reduces the deterioration of battery performance. It is even more desirable that the moisture content be 500 ppm or less.
[0215] When using the above lubricant, it is particularly preferable that it be a low-polarity solvent such as heptane or xylene, or an ionic liquid.
[0216] When using the above lubricant, the amount may be 5.0 to 35.0 parts by mass, preferably 10.0 to 30.0 parts by mass, more preferably 15.0 to 25.0 parts by mass, based on the total mass of the raw material composition provided to process (a1).
[0217] As described above, it is preferable that the above raw material composition substantially does not contain a liquid medium. Conventional methods for forming composites for secondary batteries generally involve preparing a slurry in which a powder component of the composite for secondary batteries is dispersed using a solvent in which a binder is dissolved, and preparing a composite sheet for secondary batteries by coating and drying the slurry. In this case, a solvent capable of dissolving the binder is used. However, the solvents capable of dissolving binder resins that have been generally used in the past are limited to specific solvents such as butyl butyrate. Since these react with the solid electrolyte and degrade the solid electrolyte, they may cause a decrease in battery performance. Furthermore, in low-polarity solvents such as heptane, not only are the binder resins that dissolve very limited, but the flash point is also low, which can make handling cumbersome.
[0218] In the powdered raw material composition obtained by the above process (a1), it is preferable that the content of the liquid medium be 1 mass% or less.
[0219] In addition, the composite for secondary batteries of the present disclosure preferably has a liquid medium content of 1 mass% or less.
[0220] When forming a composite sheet for a secondary battery, a battery with low moisture content can be manufactured by using a powdered binder without using a solvent. In addition, the above manufacturing method allows for the production of a composite sheet for a secondary battery containing a binder having a fine fiber structure, and also reduces the burden of the manufacturing process by not preparing a slurry.
[0221] Process (b) is calendering or extrusion. Calendering and extrusion can be performed by known methods. By doing so, the electrode composite sheet can be formed into a shape.
[0222] Process (b) preferably includes (b1) a process of forming the composite for a secondary battery obtained by process (a) into a bulk form, and (b2) a process of calendering or extruding the composite for a secondary battery in bulk form.
[0223] Bulk molding means forming the composite material for secondary batteries into a single mass.
[0224] Specific methods for forming in bulk include extrusion molding and press molding.
[0225] In addition, the term "bulk form" does not require a specific shape, but simply needs to be in a state of being in a single mass, and includes forms such as rod-shaped, sheet-shaped, spherical, and cube-shaped forms. The size of the mass is preferably such that the diameter of its cross-section or at least one side is 10,000 μm or more. More preferably, it is 20,000 μm or more.
[0226] As a specific method of calendering or extrusion molding in the above process (b2), a method of rolling a composite material for a secondary battery using a roll press, a calender roll machine, etc. can be cited.
[0227] The above process (b) is preferably carried out at 30 to 150°C. As described above, PTFE has a glass transition temperature around 30°C, so it is easily fibrillated at 30°C or higher. Therefore, it is preferable to carry out the process (b) at such a temperature.
[0228] Furthermore, during calendering or extrusion, since shear force is applied, the PTFE is fibrillated, and molding is achieved.
[0229] After process (b), it is also desirable to have process (c) in which a greater load is applied to the obtained rolled sheet to roll it into a thinner sheet. It is also desirable to repeat process (c). In this way, rather than thinning the rolled sheet all at once, the flexibility is improved by rolling it little by little in stages.
[0230] As for the number of process (c), it is preferable to have 2 or more and 10 or fewer times, and more preferable to have 3 or more and 9 or fewer times.
[0231] Specific rolling methods include, for example, a method of processing into a thinner sheet by rotating two or more rolls and passing a rolled sheet between them.
[0232] In addition, from the perspective of adjusting the fibril diameter, it is also desirable to have a process (d) in which, after process (b) or process (c), the rolled sheet is crushed, then formed back into a bulk form, and rolled into a sheet form. It is also desirable to repeat process (d). As for the number of times process (d) is performed, it is desirable to perform it 1 to 12 times, and more desirable to perform it 2 to 11 times.
[0233] In process (d), specific methods for crushing the rolled sheet and forming it into a bulk form include folding the rolled sheet, forming it into a rod or thin film sheet, or chipping it. In the present disclosure, "crushing" means changing the shape of the rolled sheet obtained in process (b) or process (c) into a different shape in order to roll it into a sheet in the next process, and includes cases where the rolled sheet is simply folded.
[0234] In addition, after process (d), process (c) may be performed, or it may be performed repeatedly.
[0235] In addition, uniaxial or biaxial stretching may be performed in processes (a) to (b), (c), and (d).
[0236] In addition, the fibril diameter (median) can be adjusted according to the degree of crushing in process (d).
[0237] In the above process (b), (c), or (d), the rolling rate is preferably 10% or more, more preferably 20% or more, and also preferably 80% or less, more preferably 65% or less, and more preferably 50% or less. If it falls below the above range, it takes time along with an increase in the number of rolling passes, which affects productivity. In addition, if it exceeds the above range, there is a risk that excessive fibrillation will occur, resulting in a composite sheet with reduced strength and flexibility.
[0238] Furthermore, the rolling rate referred to herein indicates the rate of reduction in thickness after processing relative to the thickness of the sample before rolling. The sample before rolling may be a bulk raw material composition or a sheet raw material composition. The thickness of the sample refers to the thickness in the direction in which the load is applied during rolling.
[0239] The above processes (c) to (d) are preferably performed at 30°C or higher, and more preferably at 60°C or higher. Additionally, it is preferable to perform them at 150°C or lower.
[0240] As described above, the fibrillated resin used as a binder becomes fibrillated by applying shear force. In order to have a fibrous structure with a fibrillation diameter (median value) of 100 nm or less, excessive shear stress can cause fibrillation to be excessively promoted, which may impair flexibility. In addition, weak shear stress may result in insufficient strength. Therefore, by applying an appropriate shear stress to the fibrillated resin during mixing or rolling to promote fibrillation, and by performing the process of rolling the resin to stretch it into a sheet within the above range, it is possible to have a fibrous structure with a fibrillation diameter (median value) of 100 nm.
[0241] As described above, the composite sheet for a secondary battery of the present disclosure may be either a positive electrode sheet or a negative electrode sheet. In addition, it may be a sheet for a solid electrolyte layer.
[0242] When using a composite sheet for a positive electrode or a sheet for a negative electrode, in the manufacture of the composite sheet for the secondary battery, the positive electrode active material or the negative electrode active material can be mixed together with a binder.
[0243] The positive and negative poles are explained below.
[0244] (Straight play)
[0245] In the present disclosure, the positive electrode is preferably composed of a current collector and a positive electrode sheet.
[0246] As materials for the current collector for the positive electrode, metal materials such as aluminum, titanium, tantalum, stainless steel, nickel, or their alloys; and carbon materials such as carbon cloth or carbon paper may be used. Among these, metal materials, particularly aluminum or its alloys, are preferred.
[0247] As for the shape of the entire current collector, for metal materials, examples include metal foil, metal cylinder, metal coil, metal plate, expanded metal, punched metal, foamed metal, etc., and for carbon materials, examples include carbon plate, carbon thin film, carbon cylinder, etc. Among these, metal foil is preferred. In addition, the metal foil may be appropriately formed into a mesh shape.
[0248] The thickness of the metal foil is arbitrary, but is typically 1 μm or more, preferably 3 μm or more, more preferably 5 μm or more, and also typically 1 mm or less, preferably 100 μm or less, more preferably 50 μm or less. If the metal foil is thinner than this range, it may lack the strength required as a current collector. Conversely, if the metal foil is thicker than this range, handling properties may be compromised.
[0249] In addition, it is desirable to have a conductive aid applied to the surface of the current collector, in order to reduce the electrical contact resistance between the current collector and the positive electrode composite sheet. Examples of conductive aids include carbon and precious metals such as gold, platinum, and silver.
[0250] The positive electrode can be manufactured using conventional methods. For example, methods such as laminating the positive electrode sheet and the current collector with an adhesive interposed therebetween and drying can be used.
[0251] The density of the positive electrode sheet is preferably 2.0 g / cm³ or higher, more preferably 2.1 g / cm³ or higher, and even more preferably 2.3 g / cm³ or higher, and is also preferably 4.0 g / cm³ or lower, more preferably 3.9 g / cm³ or lower, and even more preferably 3.8 g / cm³ or lower. If it exceeds this range, the conductivity between active materials decreases and the battery resistance increases, which may result in a failure to obtain high output. If it falls below this range, the content of hard and brittle active materials is low, which may result in a battery with low capacity.
[0252] The thickness of the positive electrode is not particularly limited, but from the perspective of high capacity and high power, the thickness of the composite sheet after subtracting the thickness of the current collector is preferably 10 μm or more, more preferably 20 μm or more, as a lower limit with respect to one side of the current collector, and also preferably 500 μm or less, more preferably 450 μm or less.
[0253] In addition, a material with a different composition may be attached to the surface of the above positive electrode. Examples of surface-attached materials include oxides such as aluminum oxide, silicon oxide, titanium oxide, zirconium oxide, magnesium oxide, calcium oxide, boron oxide, antimony oxide, and bismuth oxide; sulfates such as lithium sulfate, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate, and aluminum sulfate; carbonates such as lithium carbonate, calcium carbonate, and magnesium carbonate; and carbon.
[0254] (Polar)
[0255] In the present disclosure, the negative electrode is preferably composed of a current collector and a negative electrode sheet.
[0256] As materials for the current collector for the negative electrode, metal materials such as copper, nickel, titanium, tantalum, stainless steel, or their alloys; and carbon materials such as carbon cloth or carbon paper may be used. Among these, metal materials, particularly copper, nickel, or their alloys, are preferred.
[0257] Examples of shapes for the current collector include metal foil, metal cylinder, metal coil, metal plate, expanded metal, punched metal, foamed metal, etc. for metal materials, and carbon plate, carbon thin film, carbon cylinder, etc. Among these, a metal foil is preferred. Additionally, the metal foil may be formed into a mesh shape as appropriate. The thickness of the metal foil is arbitrary, but is typically 1 μm or more, preferably 3 μm or more, more preferably 5 μm or more, and typically 1 mm or less, preferably 100 μm or less, more preferably 50 μm or less. If the metal foil is thinner than this range, it may lack the strength required as a current collector. Conversely, if the metal foil is thicker than this range, handling properties may be compromised.
[0258] The negative electrode can be manufactured using conventional methods. For example, methods such as laminating the negative electrode sheet and the current collector with an adhesive interposed therebetween and drying them may be used.
[0259] The density of the negative electrode sheet is preferably 1.3 g / cm³ or higher, more preferably 1.4 g / cm³ or higher, and even more preferably 1.5 g / cm³ or higher, and is also preferably 2.0 g / cm³ or lower, more preferably 1.9 g / cm³ or lower, and even more preferably 1.8 g / cm³ or lower. If it exceeds this range, the permeability of the solid electrolyte to the vicinity of the interface between the current collector and the active material decreases, and in particular, charge / discharge characteristics at high current densities deteriorate, which may result in failure to obtain high output. Furthermore, if it falls below this range, the conductivity between the active materials decreases, increasing battery resistance, which may result in failure to obtain high output.
[0260] The thickness of the negative electrode is not particularly limited, but from the perspective of high capacity and high power, the thickness of the composite sheet after subtracting the thickness of the metal foil of the current collector is preferably 10 μm or more, more preferably 20 μm or more, and also preferably 500 μm or less, more preferably 450 μm or less, as a lower limit with respect to one side of the current collector.
[0261] (Solid-state secondary battery)
[0262] The present disclosure is also a solid secondary battery having the composite sheet for the secondary battery.
[0263] The secondary battery of the present disclosure may be a solid-state secondary battery or a secondary battery using an electrolyte.
[0264] (Solid-state secondary battery)
[0265] As for the solid secondary battery, it may be an all-solid secondary battery, or a hybrid solid secondary battery combining a gel-type polymer electrolyte and a solid electrolyte.
[0266] In addition, it is preferable that the solid-state secondary battery be a lithium-ion solid-state secondary battery.
[0267] The solid secondary battery of the present disclosure is a solid secondary battery comprising a positive electrode, a negative electrode, and a solid electrolyte layer interposed between said positive electrode and said negative electrode, wherein the positive electrode, negative electrode, and solid electrolyte layer contain a positive electrode sheet, a negative electrode sheet, or a solid electrolyte layer sheet, which is a composite sheet for a secondary battery of the present disclosure described above. Furthermore, the solid secondary battery of the present disclosure may use a material other than the composite sheet for a secondary battery of the present disclosure in a part of the positive electrode, negative electrode, and solid electrolyte layer.
[0268] The stacked structure of the solid secondary battery of the present disclosure comprises a positive electrode having a positive electrode sheet and a positive electrode current collector, a negative electrode having a negative electrode sheet and a negative electrode current collector, and a solid electrolyte layer fitted and supported on the positive electrode and the negative electrode.
[0269] Hereinafter, a separator and a battery case used in a solid-state secondary battery according to the present disclosure will be described in detail.
[0270] (Separator)
[0271] The solid secondary battery of the present disclosure may be provided with a separator between the positive electrode and the negative electrode. Examples of the separator include a porous membrane such as polyethylene or polypropylene; and a nonwoven fabric such as a nonwoven fabric made of a resin such as polypropylene or a glass fiber nonwoven fabric.
[0272] (Battery Design)
[0273] The solid secondary battery of the present disclosure may further comprise a battery case. The shape of the battery case used in the present disclosure is not particularly limited as long as it is capable of accommodating the positive electrode, negative electrode, and electrolyte layer for the solid battery described above, but specifically, cylindrical, prismatic, coin, laminated types, etc., may be presented.
[0274] The method for manufacturing a solid secondary battery of the present disclosure may, for example, first stack the positive electrode, the solid electrolyte layer sheet, and the negative electrode in sequence and press them to form a solid secondary battery.
[0275] By using the composite sheet for secondary batteries disclosed in the present disclosure, it is possible to manufacture a solid secondary battery in a state with low moisture content in the system, and it is suitable for producing a solid secondary battery having good performance.
[0276] (Secondary battery using electrolyte)
[0277] An electrode manufactured using the composite sheet for a secondary battery of the present disclosure can be used as a positive or negative electrode in various secondary batteries using an electrolyte. The secondary battery is a battery using a non-aqueous electrolyte, and examples include lithium-ion batteries.
[0278] (Electrolyte)
[0279] As the above-mentioned non-aqueous electrolyte, a known electrolyte salt dissolved in a known organic solvent for dissolving electrolyte salts may be used.
[0280] As an organic solvent for dissolving electrolyte salts, one or more types of known hydrocarbon solvents such as propylene carbonate, ethylene carbonate, butylene carbonate, γ-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, dimethyl carbonate, diethyl carbonate, ethylmethyl carbonate, etc., which are not particularly limited, and fluorine-based solvents such as fluoroethylene carbonate, fluoroether, fluorinated carbonate, etc. may be used.
[0281] Examples of electrolyte salts include LiClO4, LiAsF6, LiBF4, LiPF6, LiN(SO2CF3)2, LiN(SO2C2F5)2, etc., and LiPF6, LiBF4, LiN(SO2CF3)2, LiN(SO2C2F5)2, or combinations thereof are particularly preferred due to their good cycling characteristics.
[0282] The concentration of the electrolyte salt must be at least 0.8 mol / liter, and furthermore at least 1.0 mol / liter. The upper limit varies depending on the organic solvent used to dissolve the electrolyte salt, but is typically 1.5 mol / liter or less.
[0283] (Battery Design)
[0284] The electrode composite group may be either a laminated structure in which the positive electrode and the negative electrode are formed with a separator interposed, or a structure in which the positive electrode and the negative electrode are wound in a spiral shape with the separator interposed.
[0285] (Separator)
[0286] The material or shape of the above separator is not particularly limited as long as it is stable in the electrolyte and has excellent liquid retention properties, and known materials may be used. For example, resins, glass fibers, inorganic materials, etc. are used, and it is preferable to use a porous sheet or non-woven fabric-like form with excellent liquid retention properties.
[0287] As materials for resins and glass fiber separators, for example, polyolefins such as polyethylene and polypropylene, aromatic polyamides, PTFE, polyethersulfone, glass filters, etc., may be used. These materials, such as polypropylene / polyethylene two-layer films and polypropylene / polyethylene / polypropylene three-layer films, may be used as a single type or two or more types may be used in any combination and ratio.
[0288] Among these, the separator is preferably a porous sheet or nonwoven fabric made of polyolefins such as polyethylene and polypropylene, in that it has good permeability of the electrolyte and shutdown effect.
[0289] In addition, when a porous material such as a porous sheet or nonwoven fabric is used as a separator, the porosity of the separator is optional, but is typically 20% or more, preferably 35% or more, and more preferably 45% or more, and is typically 90% or less, preferably 85% or less, and more preferably 75% or less. If the porosity is excessively smaller than the above range, the film resistance increases and the rate characteristics tend to deteriorate. In addition, if it is excessively larger than the above range, the mechanical strength of the separator decreases and the insulation performance tends to decrease.
[0290] In addition, the average hole diameter of the separator is arbitrary, but is typically 0.5 μm or less, preferably 0.2 μm or less, and is also typically 0.05 μm or more. If the average hole diameter exceeds the above range, short circuits are likely to occur. In addition, if it falls below the above range, the film resistance increases and rate characteristics may deteriorate.
[0291] Meanwhile, as inorganic materials, oxides such as alumina or silicon dioxide, nitrides such as aluminum nitride or silicon nitride, and sulfates such as barium sulfate or calcium sulfate are used, and they are used in the form of particles or fibers.
[0292] As for the form, a thin film shape such as a nonwoven fabric, a woven fabric, or a microporous film is used. As for the thin film shape, a pore diameter of 0.01 to 1 μm and a thickness of 5 to 50 μm is suitably used. In addition to the above independent thin film shape, a separator may be used in which a composite porous layer containing the inorganic particles is formed on the surface of the positive electrode and / or negative electrode using a resin-based binder.
[0293] For example, a porous layer can be formed on both sides of the positive electrode using fluoropolymer resin as a binder, with 90% of the alumina particles having a particle size of less than 1 μm.
[0294] The material of the outer casing is not particularly limited as long as it is a material that is stable with respect to the electrolyte used. Specifically, metals such as nickel-plated steel sheets, stainless steel, aluminum or aluminum alloys, and magnesium alloys, or laminated films of resin and aluminum foil are used. From the perspective of weight reduction, metals such as aluminum or aluminum alloys and laminated films are suitably used.
[0295] In the case of an exterior case using metals, examples include forming a sealed structure by welding metals together using laser welding, resistance welding, or ultrasonic welding, or forming a swaged structure using the said metals with a resin gasket interposed. In the case of an exterior case using the said laminate film, examples include forming a sealed structure by thermally fusing the resin layers together. To improve sealability, a resin different from the resin used in the laminate film may be interposed between the said resin layers. In particular, when forming a sealed structure by thermally fusing the resin layers with a current collection terminal interposed, since the metal and resin are bonded, a resin having polar groups or a modified resin having polar groups introduced is suitably used as the interposed resin.
[0296] The shape of the secondary battery is arbitrary, and examples include cylindrical, prismatic, laminated, coin, and large shapes. In addition, the shape and configuration of the positive electrode, negative electrode, and separator can be changed according to the shape of each battery.
[0297] Examples
[0298] The present disclosure will be described in detail below based on examples.
[0299] In the following examples, unless otherwise specifically stated, “parts” and “%” represent “parts by mass” and “mass%”, respectively.
[0300] [Production Example 1]
[0301] At the point when 367 g of TFE (35.6 mass% relative to the total polymerization amount of 1032 g of TFE) was consumed from the start of polymerization, an aqueous solution of 12.0 mg of hydroquinone dissolved in 20 ml of water as a radical scavenger was injected into the TFE (concentration of 4.0 ppm relative to the aqueous medium). Polymerization continued thereafter, and when the polymerization amount of TFE reached 1000 g from the start of polymerization, the supply of TFE was stopped, the gas in the system was immediately released to atmospheric pressure, and the polymerization reaction was terminated to obtain a polytetrafluoroethylene aqueous dispersion (solid content 31.2 mass%). The obtained polytetrafluoroethylene aqueous dispersion was diluted to a solid content concentration of 15% and solidified by quietly stirring in the presence of nitric acid in a vessel equipped with a stirrer. The solidified polytetrafluoroethylene was separated and dried at 160°C for 18 hours to obtain powdered PTFE-1.
[0302] [Production Example 2]
[0303] Powdered PTFE-2 was prepared by referring to Adjustment Example 1 of International Patent No. 2012-063622.
[0304] The physical properties of the manufactured PTFE are shown in Table 1.
[0305]
[0306] (Example 1)
[0307] Positive electrode active material LiNi 0.8 Mn 0.1 Co 0.1 O2, a sulfide-based solid electrolyte LPSCl (average particle size: 8 μm), and powdered PTFE-1 were weighed and homogenized by mixing with a high-speed mixer (500 rpm, 1 minute). Stirring was performed by cooling the container to 10°C. Afterward, the mixture was mixed by stirring with a high-speed mixer (10,000 rpm, 3 minutes) to obtain a composite for a secondary battery. Stirring was performed by heating the container to 60°C. Additionally, powdered PTFE-1 was used after drying in a vacuum dryer at 50°C for 1 hour. Powdered PTFE was previously sieved using a stainless steel sieve with a mesh size of 500 μm, and the material remaining on the sieve was used.
[0308] The composition ratio was set to a mass ratio of positive electrode active material:solid electrolyte:binding agent = 85.2:14:0.8.
[0309] The obtained composite for secondary batteries was molded into a bulk form and calendered into a sheet form. Calendering was performed by heating to 80°C.
[0310] Subsequently, the obtained rolled sheet was crushed by folding it in half, formed back into a bulk form, and then rolled into a sheet using metal rolls on a flat plate to promote fibrillation; this process was repeated four times. Afterward, further rolling was performed to obtain a composite sheet for a secondary battery with a thickness of 500 μm. Additionally, the composite sheet for the secondary battery was cut, fed into a press machine, and rolled. Furthermore, the thickness was adjusted by repeatedly applying a load of 5 kN. The gap was adjusted so that the final thickness of the composite sheet for the secondary battery was 150 μm. Additionally, the above operation was performed inside an Ar glow box (dew point approximately -80°C). The rolling rate in the first pass was the highest at 39%.
[0311] (Example 2)
[0312] Positive electrode active material LiNi 0.5 Mn 1.5 O4, oxide-based solid electrolyte Li 1.3 Al 0.3 Ti 1.7 P3O 12 Weighed powdered PTFE-1 and sheet molding was performed in the same procedure as in Example 1.
[0313] The composition ratio was set so that the positive electrode active material:solid electrolyte:binding agent mass ratio was 80.2:19:0.8.
[0314] (Example 3)
[0315] Conductivity aid (acetylene black) and positive electrode active material LiNi 0.8 Mn 0.1 Co 0.1 O2 and powdered PTFE-1 were weighed, and sheet molding was performed in the same procedure as in Example 1.
[0316] It was adjusted to the composition ratio listed in Table 2.
[0317] (Example 4)
[0318] Oxide-based solid electrolyte Li 6.25 La3Zr2Al 0.25 O 12 Weighing powdered PTFE-2 and sheet molding were performed in the same procedure as in Example 1. The composition ratio was set so that the solid electrolyte:binding agent was 98.5:1.5 by mass ratio.
[0319] (Example 5)
[0320] Positive electrode active material LiNi 0.8 Mn 0.1 Co 0.1 O2, a conductive additive (carbon black: Super P Li), and powdered PTFE-4 were weighed and stirred with a high-speed mixer (10,000 rpm, for 4 minutes) to obtain a mixture. Stirring was performed by heating the container to 60°C.
[0321] In addition, powdered PTFE-4 was dried in a vacuum dryer at 50°C for 1 hour. The powdered PTFE was previously sieved using stainless steel sieves with mesh sizes of 425 µm and 355 µm, and the material that passed through the 425 µm sieve and remained on the 355 µm sieve was used. The composition ratio was adjusted as indicated in Table 2.
[0322] The obtained mixture was formed into a bulk form and rolled into a sheet. Rolling was performed at room temperature.
[0323] Afterwards, the previously obtained rolled sheet was crushed by folding it into two pieces, formed back into a bulk form, and then rolled into a sheet using a metal roll on a flat plate to promote fibrillation, a process of repeating this three times. Subsequently, by further rolling, a composite sheet for a secondary battery with a thickness of 500 μm was obtained. In addition, the composite sheet for the secondary battery was cut, fed into a press machine, and rolled. Furthermore, the thickness was adjusted by repeatedly applying a load of 5 kN. The gap was adjusted so that the final thickness of the composite sheet for the secondary battery was 150 μm.
[0324] Each test was conducted using the following methods.
[0325] [Measurement of moisture content]
[0326] Powdered PTFE was dried in a vacuum dryer at 50°C for 1 hour. The moisture content of the PTFE after vacuum drying was measured using a Karl Fischer moisture meter (ADP-511 / MKC-510N, manufactured by Kyoto Denshi Kogyo Co., Ltd.) equipped with a boat-type moisture vaporizer. The moisture was heated to 210°C in the moisture vaporizer to measure the vaporized moisture. Nitrogen gas was flowed as a carrier gas at a flow rate of 200 mL / min, and the measurement time was set to 30 minutes. Additionally, ChemAqua was used as the Karl Fischer reagent. The sample weight was 1.5 g.
[0327] [Median Fibril Diameter of PTFE]
[0328] (1) An image is obtained by taking a magnified photograph (7000x) of a composite sheet for a secondary battery using a scanning electron microscope (S-4800 type, manufactured by Hitachi Seisakusho Co., Ltd.).
[0329] (2) Divide the image into three equal parts by drawing two lines horizontally at equal intervals.
[0330] (3) For all PTFE fibers on the straight line above, the diameter of each PTFE fiber is measured at three locations, and the average value is taken as the diameter of the PTFE fiber. The three measurement locations are selected as the intersection point between the PTFE fiber and the straight line, and locations offset by 0.5 μm upward and downward from the intersection point (excluding primary PTFE particles that have undergone microfiberization).
[0331] (4) The above operation (3) is performed on all PTFE fibers in the straight line below.
[0332] (5) Move 1 mm to the right of the screen starting from the first image and take another picture, and measure the diameter of the PTFE fibers according to (3) and (4) above. Repeat this process until the number of measured fibers exceeds 80, at which point the process ends.
[0333] (6) The median value of the diameters of all PTFE fibers measured above was taken as the size of the fibril diameter.
[0334] [Flexibility Assessment]
[0335] The fabricated composite sheet for secondary batteries was cut into pieces measuring 2 cm in length and 6 cm in width to serve as test specimens. After being wound onto a round bar with a diameter of 4 mm, the test specimens were visually inspected and evaluated according to the following criteria. If no defects or cracks were found, it was rated as ○; if cracks were found, it was rated as ×.
[0336] [Intensity Measurement]
[0337] Measurements were taken using a digital force gauge (Imada ZTS-20N) on a 4 mm wide rectangular electrode composite test specimen under conditions of 100 mm / min. The spacing between the rods was set to 30 mm. Displacement was applied until fracture, and the maximum stress of the measured result was taken as the strength of each sample. The test was performed 5 times, and the average value was taken as the strength.
[0338] The test results are shown in Table 2.
[0339]
[0340] From the results of Table 2, composite sheets can be produced even with a small amount of binder, and the composite sheet for secondary batteries in the example had excellent physical properties. By performing homogenization at a low temperature, the dispersibility of PTFE can be further enhanced while suppressing the generation and growth of fibrils. In addition, by heating during molding, the generation of fibrils can be increased, and the entanglement of fibrils is promoted, allowing for the production of a sheet with high strength. Furthermore, by increasing the secondary particle size of the PTFE powder, the handling properties of the powder are also excellent.
[0341] As described above, by the method for manufacturing a composite sheet of the present disclosure, the binder can be made to a specific fibril diameter, and a composite sheet with high strength can be obtained even if the amount of binder is small. Industrial applicability
[0342] The composite for secondary batteries and the composite sheet for secondary batteries containing the same of the present disclosure can be used in the manufacture of secondary batteries.
Claims
Claim 1 A composite for a solid secondary battery containing a solid electrolyte and / or an electrode active material and a binder, wherein the binder is a fibrillic resin having a fibrous structure with a fibrill diameter (median value) of 70 nm or less, and is characterized in that it is included in an amount of 0.3 mass% or more and 1.5 mass% or less in the composite for the solid secondary battery. Claim 2 A composite for a solid secondary battery according to claim 1, wherein the fibril resin is polytetrafluoroethylene resin. Claim 3 A solid secondary battery composite obtained using a raw material composition containing a solid electrolyte and / or an electrode active material and a binder, wherein the binder in the raw material composition is a powdered fibrilable resin. Claim 4 In paragraph 3, the powdered fibril resin is a composite for solid secondary batteries having a moisture content of 500 ppm or less. Claim 5 A composite for a solid secondary battery according to paragraph 3, wherein the powdered fibril resin is a powdered polytetrafluoroethylene resin. Claim 6 In claim 5, the powdered polytetrafluoroethylene resin is a composite for solid secondary batteries having a standard specific gravity of 2.12 to 2.
20. Claim 7 In claim 5, the powdered polytetrafluoroethylene resin comprises 80 mass% or more of a polytetrafluoroethylene resin having a secondary particle size of 450 μm or more, for use in a solid secondary battery. Claim 8 A composite for a solid secondary battery electrode according to claim 1 or 2, comprising a solid electrolyte, an electrode active material, and a binder. Claim 9 A composite sheet for a solid secondary battery comprising the composite for a solid secondary battery described in claim 1 or 2. Claim 10 An electrode comprising a sheet of a composite material for a solid secondary battery electrode comprising the composite material for a solid secondary battery electrode described in claim 8. Claim 11 A method for manufacturing a composite sheet for a solid secondary battery, comprising a solid electrolyte and / or an electrode active material and a binder, wherein the binder is a fibril-like resin having a fibrous structure with a fibril diameter (median value) of 70 nm or less, and is included in the composite sheet for a solid secondary battery in an amount of 0.3 mass% or more and 1.5 mass% or less, wherein the method comprises: a step of mixing the solid electrolyte and / or an electrode active material and the binder to form a composite sheet for a solid secondary battery; and a step of calendering or extruding the composite sheet for a solid secondary battery to manufacture a sheet, wherein the mixing of step (a) comprises: (a1) a step of homogenizing the solid electrolyte and / or an electrode active material and the binder to form a powder; and (a2) a step of mixing the powdered raw material composition obtained by step (a1) to prepare a composite sheet for a solid secondary battery. Claim 12 A method for manufacturing a composite sheet for a solid secondary battery according to claim 11, wherein homogenization in process (a1) is performed at a temperature of 19°C or lower, and mixing in process (a2) is performed at a temperature of 30°C or higher. Claim 13 A method for manufacturing a composite sheet for a solid secondary battery according to claim 11, wherein process (b) is to perform calendering or extrusion at a temperature of 30 to 150°C. Claim 14 A method for manufacturing a composite sheet for a solid secondary battery, wherein, in claim 11 or 12, the mixing in process (a) is performed while applying shear force. Claim 15 A secondary battery having a composite sheet for a solid secondary battery as described in claim 9. Claim 16 delete
Citation Information
Patent Citations
Preparation and processing method of solid electrolyte membrane
CN112421114A
Solid electrolyte composition, solid electrolyte-containing sheet and all-solid-state secondary battery, and method for manufacturing the solid electrolyte-containing sheet and all-solid-state secondary battery
KR1020190002550A
